Pengaruh Motivasi Dan Pengetahuan Kewirausahaan Terhadap Minat Berwirausaha Siswi XII Akuntansi 1 SMK Darussalam Blokagung Banyuwangi - Suprapto, Ribut; Susanti, Nawal Ika; Putri, Siti Qoimatus Sarofah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
This study aims to determine whether or not there is a positive influence between motivation and entrepreneurial knowledge on the entrepreneurial interest of XII Accounting 1 student at Darussalam Blokagung Banyuwangi Vocational School. The data analysis tool used in this research is multiple regression analysis. This type of research is quantitative. Where the methods used to collect data include observation, interviews, documentation and questionnaires / questionnaires. Based on the results of this study, it shows that the variables X1 and X2 have a significant effect on the Y variable with an R value of 0.745 with a significance of 20.544 > 3.28. Dimensions of motivation and knowledge of entrepreneurship simultaneously influence the interest in entrepreneurship, significantly. The motivational variable produces an F count value of 0.546 and entrepreneurial knowledge of 0.487 with a significance value greater than 0.05 meaning that it simultaneously influences the interest in entrepreneurship for XII Accounting 1 students of SMK Darussalam Blokagung Banyuwangi.